Linchpin - men, middle managers and gender inclusive leadership - Kelan, Elisabeth (Cranfield University, 2016)
The final report from an extensive research project on how men as middle managers can engage in gender inclusive leadership.
Keywords: 'inclusion'; 'men'; 'gender equality'; 'diversity'; 'leadership'; 'middle management'; 'gender inclusivity'; 'Organisation and Management Theory'; 'Business and Management not elsewhere classified'